2018
DOI: 10.1002/aoc.4604
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)‐based ethylene dimerization catalysts with silicon‐bridged diphosphine ligands

Abstract: A series of ligands and cobalt complexes were synthesized and characterized using NMR spectroscopy, elemental analysis and single-crystal X-ray diffrac-features a monomeric structure with κ 2 coordination of the silicon-bridged diphosphine ligand to the cobalt center.Using dried methylaluminoxane (DMAO) and AlEt 3 as co-catalysts and methylcyclohexane as solvent, the Co(II) complex proved to be moderately active and highly selective for ethylene dimerization. The effects of ligand structure, catalyst loading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Complexes 46 and 47, activated by MMAO, were capable of producing ethylene oligomers with moderate activity (up to 5.1 × 10 5 g•mol −1 Co •h −1 for complex 47) in which α-C 8 was the major product. Jiang and co-workers [139] reported a series of cobalt complexes featuring a monomeric structure with the silicon-bridged diphosphine ligand to the cobalt center (Figure 14). Transition metals supported with diphosphine ligands can exhibit good catalytic performance due to their singly and weakly coordinating moieties that can readily dissociate to create a vacant site for coordination, thereby enhancing the catalytic activity [140,141].…”
Section: Tri-dentate Cobalt Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes 46 and 47, activated by MMAO, were capable of producing ethylene oligomers with moderate activity (up to 5.1 × 10 5 g•mol −1 Co •h −1 for complex 47) in which α-C 8 was the major product. Jiang and co-workers [139] reported a series of cobalt complexes featuring a monomeric structure with the silicon-bridged diphosphine ligand to the cobalt center (Figure 14). Transition metals supported with diphosphine ligands can exhibit good catalytic performance due to their singly and weakly coordinating moieties that can readily dissociate to create a vacant site for coordination, thereby enhancing the catalytic activity [140,141].…”
Section: Tri-dentate Cobalt Complexmentioning
confidence: 99%
“…Transition metals supported with diphosphine ligands can exhibit good catalytic performance due to their singly and weakly coordinating moieties that can readily dissociate to create a vacant site for coordination, thereby enhancing the catalytic activity [140,141]. Jiang and co-workers [139] reported a series of cobalt complexes featuring a monomeric structure with the silicon-bridged diphosphine ligand to the cobalt center (Figure 14). Transition metals supported with diphosphine ligands can exhibit good catalytic performance due to their singly and weakly coordinating moieties that can readily dissociate to create a vacant site for coordination, thereby enhancing the catalytic activity [140,141].…”
Section: Tri-dentate Cobalt Complexmentioning
confidence: 99%
“…We recently found that the ligands having PNP scaffolds such as PNSiP, PNSiCP, and PN (CH 2 ) n P behave as efficient catalytic systems for selective ethylene tri-/ tetramerization. [13][14][15][16][17][18] To further elucidate the potential role of the PNP scaffold toward ethylene oligomerization, we, herein, reported three new PNP-based L 1 -L 3 ligands with PNP (NR 2 ) 2 scaffold, which upon coordination with CrCl 3 (THF) 3 correspondingly afforded 1-3 chromium complexes (Scheme 1). Upon activation with MMAO-3A, the 1-3 complexes when scrutinized for ethylene oligomerization offered efficient catalysts for selective ethylene tri-/tetramerization.…”
Section: Introductionmentioning
confidence: 99%